The Role of Gapoktan Bakti in Increasing the Income of Rubber Farmers in Anggokoti Village, Buke District, South Konawe Regency - Oryzy, Jucky Marzuki Phyty; Fyka, Samsul Alam; Arif, La Ode Kasno (International Journal of Technology and Education Research, 2025)
This study aims to find out the function of Gapoktan Bakti in Anggokoti Village, find out the level of income obtained by rubber farmers in Anggokoti village and find out the relationship between the function of Gapoktan Bakti and the income of rubber farmers in Anggokoti Village. The population in this study includes individuals who are members of Gapoktan Bakti and have their own rubber plantations, totaling 21 people, with the sampling method being saturated sampling, where the entire population is used as a sample. The variables in this study are the function of gapoktan and farmers' income. The first data analysis technique uses descriptive analysis to determine the function of Gapoktan Bakti in Anggkoti Village. The second analysis technique uses income analysis to determine the income level of rubber farmers in Anggkoti Village. The third analysis technique uses Spearman rank correlation analysis to determine the relationship between the function of Gapoktan Bakti and the income of rubber farmers in Anggkoti Village. The results of the study show that (1) The implementation of the function of Gapoktan Bakti as a unit providing production facilities and infrastructure consists of fulfilling agricultural facilities (fertilizers, herbicides, and rubber vinegar), agricultural equipment (sapping knives and rubber pryers), and making it easier for farmers to access agricultural facilities, obtaining an average score (2.25) which is in the medium category. The implementation of Gapoktan Bakti's function as a farming/production unit consists of improving farmers' ability in rubber tapping activities , maintaining rubber plants, and maintaining the cleanliness of rubber sap, obtaining an average score (1.74) which is in the medium category. The implementation of Gapoktan Bakti's function as a marketing unit consists of stabilizing the selling price of rubber through partnerships, facilitating rubber marketing activities, and providing information on rubber prices, obtaining an average score (2.12) which is in the medium category. (2) The income level of rubber farmers in Anggokoti Village is quite high with an average of Rp 33,275,833,-/ha/year. (3) There is a strong relationship between the implementation of the Gapoktan Bakti function and the income of rubber farmers in Anggkoti Village, with a correlation coefficient value (rs) of 0.653 and a significance of 0.001.